MODEL OF PROFESSIONAL QUALITIES FORMATION IN THE PROCESS OF PROFESSIONAL TRAINING OF FUTURE MANAGER IN THE CONTEXT OF GENDER FEATURES - Чемеринська, Д. (Київський національний університет імені Тараса Шевченка, 2019)
The article presents an model of professional qualities formation in the process of professional training of a manager at a university with in the context of gender features. The article reveals the target, methodological, organizational, informative, effective blocks of the model. It is noted that part of the methodological component is the laws built on the principles described. The final result is presented in the form of the formation of managerial qualities in a gender-sensitive environment.

Представлено модель формування професійних якостей у процесі професійної підготовки менеджера у ЗВО із врахуванням гендерних особливостей. Розкривається цільовий, методологічний, організаційний, змістовий, результативний блоки моделі. Зазначається, що частиною методологічної складової є закони, що побудовані на описаних принципах. Представлено кінцевий результат у вигляді сформованості якостей менеджера у гендерно-чутливому середовищі.
МОДЕЛЬ ФОРМУВАННЯ ПРОФЕСІЙНИХ ЯКОСТЕЙ У ПРОЦЕСІ ПРОФЕСІЙНОЇ ПІДГОТОВКИ МАЙБУТНЬОГО МЕНЕДЖЕРА З УРАХУВАННЯМ ГЕНДЕРНИХ ОСОБЛИВОСТЕЙ
Keywords: gender-sensitive environment; curriculum; model; the formation of professional qualities; vocational training; гендерно-чутливе середовище; навчальний план; модель; сформованість професійних якостей; професійна підготовка